Liposome mimicking polymersomes; A comparative study of the merits of polymersomes in terms of formulation and stability - Noorjahan Aibani; Talat N. Khan; Bridgeen Callan (Elsevier, 2020)
The past few decades have seen a significant rise in research into alternative polymer based nanosized unilamellar drug delivery systems, termed polymersomes. The reported benefits of polymersomes over the more traditional liposomes include increased stability, higher encapsulation efficacies, better adaptability and reduced water permeation due to an increased bilayer thickness. Together, these advantages render them suitable for a plethora of therapies. The work presented in this manuscript creates and compares four such drug delivery systems, two based on the traditional liposome and two prepared from amphiphilic polymers. From there we assess these systems in terms of size, stability, encapsulation efficiency, drug release, cellular toxicity and cellular uptake. We can confirm from this comprehensive investigation that the multi-functional synthetic polymersomes are undoubtedly a future contender in this expanding field of nanomedicines. Their ability to encapsulate a cocktail of different compounds, high stability as well as their ease of adaptability will ensure that they feature prominently in the future of advanced drug delivery systems.